Photoshop 7 professional photographic techniques - Shah, Vikas; Cromhout, Gavin; Costello, Nyree; Aronoff, Janee (Birmingham Friends ED, 2002)
Fully illustrated in color throughout, the text is organized into a series of examples that provides a comprehensive guide to image manipulation on Photoshop 7 -- everything from the glamour of magazine retouching, through restoration work to the nitty-gritty of color reproduction.